Zachman Enterprise Architecture Planning (Study Case: E –Government’s General Election Services on Karadenan Sub-District in Bogor Regency - Armada Rizki; Elisa Susanti; Wina Erwina (Scientific Journal of Informatics, 2023)
Purpose: This study examines enterprise architecture planning using the Zachman Framework as an effort to automate citizen administration in Bogor Regency. Furthermore, this planning is a solution in the simultaneous step of preparing voter lists down in general election commission data, especially connected to the Citizen Administration Bureau in Karadenan Sub District as a pilot plant project. This study aims to analyze enterprise architecture planning for citizen administration involved in the General Election Commission on collection, updating, and changing citizen data in Karadenan Sub District in Bogor Regency.Methods: Data analysis was carried out from 122 heads of neighborhood units and 19 heads of residential units in Karadenan Subdistrict Bogor Regency. After that, using a qualitative method using the Zachman Framework, an Enterprise Architecture Planning of Citizen Administration was designed.Result: According to the results, this study provides a new role model-based service scheme for citizen administration, especially in election conditions.Novelty: The results of this study are valuable for the government in implementing new digital citizen administration services, especially empowering general elections by providing high-quality data on voters.